Remote heteroepitaxy of GaN microrod heterostructures for deformable light-emitting diodes and wafer recycle - Jeong, Junseok (Sci Adv, 2020)
There have been rapidly increasing demands for flexible lighting apparatus, and micrometer-scale light-emitting diodes (LEDs) are regarded as one of the promising lighting sources for deformable device applications. Herein, we demonstrate a method of creating a deformable LED, based on remote heteroepitaxy of GaN microrod (MR) p-n junction arrays on c-Al(2)O(3) wafer across graphene. The use of graphene allows the transfer of MR LED arrays onto a copper plate, and spatially separate MR arrays offer ideal device geometry suitable for deformable LED in various shapes without serious device performance degradation. Moreover, remote heteroepitaxy also allows the wafer to be reused, allowing reproducible production of MR LEDs using a single substrate without noticeable device degradation. The remote heteroepitaxial relation is determined by high-resolution scanning transmission electron microscopy, and the density functional theory simulations clarify how the remote heteroepitaxy is made possible through graphene.